2012
DOI: 10.1097/moh.0b013e328353bc7d
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution after hematopoietic cell transplantation

Abstract: Lessons learned from observational studies on immune reconstitution are leading to new strategies to prevent or treat posttransplant infections. Additional knowledge is needed to develop effective strategies to prevent or treat relapse, second malignancies and GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
172
4
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(188 citation statements)
references
References 164 publications
10
172
4
2
Order By: Relevance
“…Studies in both mouse and man have indicated that the lymphopenic state is associated with a spectrum of T cell abnormalities, including spontaneous proliferation, conversion to activated/memory phenotype, and tissue infiltration and damage (1)(2)(3)(4). In addition, spontaneous proliferation is usually oligoclonal, leading to constriction of the T cell repertoire (5)(6)(7)(8). Development of protocols that allow full reconstitution of the peripheral T cell compartment without inflammatory sequelae is an important aspect of ensuring good outcomes after lymphopenia-inducing therapeutic regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both mouse and man have indicated that the lymphopenic state is associated with a spectrum of T cell abnormalities, including spontaneous proliferation, conversion to activated/memory phenotype, and tissue infiltration and damage (1)(2)(3)(4). In addition, spontaneous proliferation is usually oligoclonal, leading to constriction of the T cell repertoire (5)(6)(7)(8). Development of protocols that allow full reconstitution of the peripheral T cell compartment without inflammatory sequelae is an important aspect of ensuring good outcomes after lymphopenia-inducing therapeutic regimens.…”
Section: Introductionmentioning
confidence: 99%
“…9 In the first months, immune competence is in part restored in a thymus-independent fashion by proliferation of the T cells in response to increased levels of homeostatic cytokines or exogenous antigens. 1,10 Production of new T cells occurs only later by resumed thymic output. 10 The unmanipulated graft contains subsets of naive and memory T cells with defined specificities that display distinct proliferative and persistence capacities in response to lymphopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressants are, unfortunately, not selective for alloreactive T cells and may thus limit adaptive immune responses to opportunistic infections and cancer. 1 Depletion of T cells from the allograft prevents GVHD but results in delayed reconstitution and increased morbidity and mortality due to opportunistic infections and tumor relapse. 2 High-dose cyclophosphamide given early posttransplant (pt-Cy) has been proposed to selectively spare bystander naive and memory T cells while depleting alloreactive T cells in vivo after infusion of unmanipulated grafts.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Low B-cell counts and immunosuppression cause weak vaccination responses within the first year after transplantation. 2 Immunoglobulin quantification as a measurement of self-acquired B-cell immunity is complicated by immunoglobulin substitution and blood product transfer containing residual amounts of plasma. ELISpot analysis could be a more precise method to determine B-cell capacity to differentiate into antibody-secreting cells after in vitro stimulation and thus to estimate B-cell immunity after transplant.…”
Section: Introductionmentioning
confidence: 99%